CD36 in atherosclerosis - Acharya, Dhruba (Nepalese Heart Journal, 2013)
CD36 was described nearly 30 years ago as “glycoprotein IV” the fourth major band of 88KD observed on SDS-PAGE of platelet membrane (1). It is present on many mammalian cell types: microvascular endothelium; professional phagocytes including macrophages, dendritic cells, microglia and retinal pigment-epithellium; erythroid precursors; hepatocytes; adipocytes; cardiac and skeletal myocytes; and specialized epithelia of the breast, kidney and gut (2). As a pattern recognition receptor, CD36 binds a diverse set of ligands, including oxidized low-density lipoprotein (oxLDL)(5), anionic phospholipids (4), long-chain fatty acids, thrombospondin-1, fibrillar -amyloid, and the membrane of cells undergoing apoptosis (3, 5, 6). CD36 has been implicated in a wide variety of normal and pathologic biological functions, including angiogenesis, atherosclerosis, phagocytosis, inflammation, lipid metabolism, and removal of apoptotic cells (3, 5). In 1993, Endemann et al. first identified CD36 as a potential oxLDL receptor (7).Unlike macrophage scavenger receptor A type I and II, CD36 binds LDL that has been exposed to minimally oxidizing condition. The observation that CD36 was an oxLDL receptor was the catalyst for many to prove the role of CD36 in atherosclerosis. DOI: http://dx.doi.org/10.3126/njh.v9i1.8349 Nepalese Heart Journal Vol.9(1) 2012 pp.47-50